HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP PEKERJA TERHADAP PERILAKU K3 PADA PEKERJA PEMANDU WISATA ATV TAHUN 2026 - I Kadek Dwi Arta Saputra; Cokorde Gde Putra Pemayun; Ni Made Ayu Wulandari; Ni Putu Ardiyanti; Ni Putu Ayu Resitha Dewi (Jurnal Cakrawala Ilmiah, 2026)
ATV (All-Terrain Vehicle) tourism activities carry a high occupational health and safety (OHS) risk that demands strict supervision for both tourists and workers. On one hand, tourists are vulnerable to losing control and sustaining injuries on extreme tracks. On the other hand, tour guides face more complex risks, including physical fatigue, chronic dust exposure, and fatal injuries when evacuating guests in difficult terrain. The impact of these risks is heavily influenced by the level of OHS knowledge and attitudes of both parties. This study aims to determine the relationship between workers' knowledge level and attitude toward the occupational health and safety behavior of ATV tour guides. Methods: This study employed an analytical cross-sectional research design. The sampling technique utilized total sampling, involving all 30 ATV tour guides as respondents. The collected data consisted of primary data, which were analyzed using univariate analysis and bivariate analysis with the Chi-square test to determine the relationships. Results: The statistical test results revealed a p-value of 0.021, indicating a significant relationship between knowledge and worker behavior. Similarly, the statistical analysis showed a significant relationship between work attitude and worker behavior, with a p-value of 0.045.